Religion - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2020)
Geographies of religion have expanded in size and scope over the past three decades. They have evolved from consideration of the areal distribution of religions around the world to more sustained engagements with how religious phenomena are imprinted on the landscape. Associated with this shift has been a focus on how space is (re)produced by different religious actors (and the workings of power therein), the experiences of religion in and through space, and how religious spaces intersect with the formation of communities and identities. More recently, geographies of religion have engaged with topical debates surrounding the secularization and purported postsecularization of Western societies, and with the emergence of new forms of spirituality in the contemporary world. Combined, these developments underscore the fact that geographies of religion do not exist in isolation, but in conversation with the academic and social worlds within which they are embedded.